Impact of generative artificial intelligence on the personalization of communication in international B2B sales - Pankulych, Ivan (Актуальні питання економічних наук, 2026)
The scientific significance and relevance of the study stem from the widespread adoption of generative artificial intelligence in international sales systems, as well as the growing need for personalized communications amid the complexity of global markets, multi-level decision-making processes, and increased competitive pressure among companies. The purpose of the article is to consider the theoretical and methodological basis of the influence of generative artificial intelligence on the personalization of communication in international B2B sales, including technological, organizational and strategic factors. The study used methods of scientific literature analysis to study the current state of the problem under study; generalization and systematization to present the results of scientific research. Results. It is confirmed that generative artificial intelligence is a key element in the evolution of companies’ personalized communication with consumers, contributing to the transition from standardized messages to dynamic, contextually adapted communication solutions. Using generative models to combine customer data analysis with content creation that matches them improves the accuracy of communications in international B2B markets. It is shown that the use of intelligent algorithms to automate and scale personalized messages helps overcome communication barriers arising from cultural, linguistic, and industry differences across markets. It is determined that the implementation of generative artificial intelligence shifts the seller’s function from operational to strategic and consultative, thereby adding value to the customer. It is found that ethical, legal, and information risks reduce the effectiveness of personalized communication and require regulation at the institutional and managerial levels. Conclusions. Generative artificial intelligence forms new approaches to communication between entities in international B2B sales, combining technology with human knowledge and values. It has been shown that businesses using generative artificial intelligence in their sales strategies can improve communication, provided that ethical standards, legal requirements, and long-term goals of cooperation are met.